2020
DOI: 10.3390/v12070723
|View full text |Cite
|
Sign up to set email alerts
|

Catching Common Cold Virus with a Net: Pyridostatin Forms Filaments in Tris Buffer That Trap Viruses—A Novel Antiviral Strategy?

Abstract: The neutrophil extracellular trap (ET) is a eukaryotic host defense machinery that operates by capturing and concentrating pathogens in a filamentous network manufactured by neutrophils and made of DNA, histones, and many other components. Respiratory virus-induced ETs are involved in tissue damage and impairment of the alveolar–capillary barrier, but they also aid in fending off infection. We found that the small organic compound pyridostatin (PDS) forms somewhat similar fibrillary structures in Tris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 16 publications
(15 reference statements)
1
13
0
Order By: Relevance
“…We thus attempted to deliver PDS to the viral RNA genome within the native virion by exploiting this phenomenon. All incubations were done in phosphate-buffered saline (PBS) to prevent PDS aggregation into long brils, as we have recently observed for Tris-but not phosphate-based buffers 71 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We thus attempted to deliver PDS to the viral RNA genome within the native virion by exploiting this phenomenon. All incubations were done in phosphate-buffered saline (PBS) to prevent PDS aggregation into long brils, as we have recently observed for Tris-but not phosphate-based buffers 71 .…”
Section: Resultsmentioning
confidence: 99%
“…via forming virus-trapping laments as observed in Tris-based buffers (see above and ref. 71 ) or on the overall rate of native to subviral (A + B) particle conversion. However, quanti cation of the viral RNA contained in the 2G2 precipitates showed that the virus incubated in the presence of PDS and recovered from cells 30 min post-infection (pi) in the form of subviral A-and B-particles contained about 70 % more viral RNA than virus pre-incubated without PDS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus attempted to deliver PDS to the viral RNA genome within the native virion by exploiting this phenomenon. All incubations were done in phosphate-buffered saline (PBS) to prevent PDS aggregation into long fibrils, as we have recently observed for Tris-but not phosphate-based buffers 71 .…”
Section: Pyridostatin (Pds) and Phendc3 Reduce Rv-a2 Infectivitymentioning
confidence: 99%
“…via forming virustrapping filaments as observed in Tris-based buffers (see above and ref. 71 ) or on the overall rate of native to subviral (A + B) particle conversion. However, quantification of the viral RNA contained in the 2G2 precipitates showed that the virus incubated in the presence of PDS and recovered from cells 30 min post-infection (pi) in the form of subviral A-and B-particles contained about 70 % more viral RNA than virus pre-incubated without PDS.…”
Section: Pyridostatin (Pds) and Phendc3 Reduce Rv-a2 Infectivitymentioning
confidence: 99%